Exploring Significant Factors of Working Chinese in Shaoxing to Use Mobile Banking - Wu, Xia (Scholar: Human Sciences, 2024)
Purpose: This study aims to determine the factors that affect how Chinese customers utilize and behave when using mobile banking. The conceptual framework focuses on the relationship between perceived usefulness, trust, pricing value, user satisfaction, behavioral intention and use behavior of mobile banking applications. Research design, data, and methodology: Using a quantitative approach (n=450), the researcher distributed questionnaires to Chinese workers in Shaoxing, who have been using the Agricultural Bank of China (ABC), China Construction Bank (CCB), and Industrial and Commercial Bank of China (ICBC)’s mobile banking applications. The nonprobability sample includes judgmental sampling, quota sampling and convenience sampling. Structural Equation Modelling (SEM) and Confirmatory Factor Analysis (CFA) were used for data analysis, including model fit analysis, reliability, and construct validity. Results: The results show that perceived usefulness, pricing value, and user satisfaction have significant impacts on behavioral intention, except for trust, and perceived usefulness has a significant impact on user satisfaction, while behavioral intention has a significant impact on user behavior. Conclusions: Five hypotheses were proven to fulfill research objectives. Therefore, mobile banking application development needs to pay more attention to the perceived usefulness, pricing value, behavioral intention, and user satisfaction aspects of the research and development efforts.